Planning and developing medical tourism in megalopolis Shiraz - Masoud Safaeepour; Majid Goodarzi; Nosrat allah Rostami kondari (Management Science Letters)
Medical tourism is an international phenomenon where some tourists travel long to reach treatment-therapeutic services because of high expenses, long waits, lacking in insurance, and applying services and insufficient access to health services in the destination. This industry, now, by making 60 billion dollars annually in international level, has been considered as one the most profitable markets and the number of countries to provide facilities and treatment services for foreign tourists tend to increase. Many countries provide applicable and legal plans for development of this industry. This paper aims at planning and improving medical tourism in megalopolis Shiraz. The dominating approach in the present study is developmental-applied and the method is descriptive, analytical and survey study. To analyze the data and to test the research hypothesis, the linear Pearson correlation and ANOVA were used. The results of the present study have indicated that all quality factors of treatment and tourism services, culture, facilities, medical and tourist equipment and ICT, had positive and direct correlation with developing medical tourism and the factor of price had negative and reverse correlation with it. In other words, the higher the price is, the less the medical tourism development is and vice versa. Also, the ANOVA showed that among medical tourists from various countries regarding satisfaction with the price of treatment and tourist services, the quality of treatment and tourist services, culture, facilities, medical and tourist equipment and ICT, there are significant differences and Kuwaiti tourists were the most satisfied tourists and Afghani ones were the least satisfied.